Research on the Intelligent Construction of the Rebar Project Based on BIM - Dejiang Wang; Youyang Hu (Applied Sciences, 2022)
Rebar engineering in the construction industry lacks effective technical means and has a high processing cost and high waste rate. Under the background of intelligent construction, the centralized processing mode of steel bars in prefabricated factories realizes the automatic processing of steel bars and improves the processing efficiency of steel bars. Using the C# programming language, combined with Revit secondary development technology, the automatic generation of the rebar model and the automatic export of rebar drawing are realized, which saves time for the designers to build the model. The calculation method of the cutting length of the steel bar is analyzed in this paper, which can be used as a reference for the subsequent optimization research of steel bar cutting. The assembly position information of the steel bar was introduced into an Excel table to help realize the automatic assembly of the steel bar cage and the intelligent construction of the steel bar. Combined with mixed reality technology, project personnel can interact with the reinforced BIM model through the mixed reality device Hololens2 to guide construction remotely.